Material for Economic Experience: Feminist Management: Material Für Ökonomische Erfahrung: Feministisches Management - Falczyk, Felix; Herschel, Johanna (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Felix Falczyk and Johanna Herschel Title (English): Material for Economic Experience: Feminist Management Title (German): Material Für Ökonomische Erfahrung: Feministisches Management Translated by (German to English): Felix Falczyk and Johanna Herschel Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 135-159 Page Count: 26 Citation (English): Felix Falczyk and Johanna Herschel, “Material for Economic Experience: Feminist Management,” Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017): 135-158. Citation (German): Felix Falczyk und Johanna Herschel, “Material für ökonomische Erfahrung: Feministisches Management,” Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017): 135-159.